2015
DOI: 10.1016/j.egypro.2015.03.070
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on a Sodium Loop-type Heat Pipe for Thermal Transport from a High-temperature Solar Receiver

Abstract: A loop-type heat pipe was fabricated and tested to transport high-temperature thermal energy from a solar receiver in a CSP application. The purpose of the heat pipe in this study was to transport an 800-W thermal load at 1000 K to a specific energy conversion device 0.5 m in distance from the solar receiver. The container wall and transport lines of the loop-type heat pipe were made of stainless steel 304, and the working fluid was sodium. The evaporator and condenser were disk-type containers with diameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Brayton's receiver technologies are responsive to the aforementioned specifications, while employing different technology elements tested under previous DOE programs. Alkali metal heat pipe solar absorbers have been analyzed and tested by DOE contractors under the ASCS [9] program, Sandia National Labs, NASA, Argonne National Labs, Los Alamos National Labs [10], and other institutions [11] over a three decade period. Gas-heating solar receivers have likewise received significant attention over past decades for Brayton, Stirling, and indirect cycles, and recently have been identified by the DOE as one of the three likely technology paths towards the next generation receiver for use with high efficiency CSP systems.…”
Section: Executive Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Brayton's receiver technologies are responsive to the aforementioned specifications, while employing different technology elements tested under previous DOE programs. Alkali metal heat pipe solar absorbers have been analyzed and tested by DOE contractors under the ASCS [9] program, Sandia National Labs, NASA, Argonne National Labs, Los Alamos National Labs [10], and other institutions [11] over a three decade period. Gas-heating solar receivers have likewise received significant attention over past decades for Brayton, Stirling, and indirect cycles, and recently have been identified by the DOE as one of the three likely technology paths towards the next generation receiver for use with high efficiency CSP systems.…”
Section: Executive Summarymentioning
confidence: 99%
“…A model is needed that can quickly and accurately calculate these output parameters for various receiver geometries. A finite difference model was created in EES that discretizes one side of one cell in the receiver into 5 nodes in width, and 20 nodes in length [11]. Since the nose sees a significant flux, it too is discretized into 5 nodes radially and 20 nodes in length.…”
Section: Receiver Designmentioning
confidence: 99%
“…Brayton's receiver technologies are responsive to the aforementioned specifications, while employing different technology elements tested under previous DOE programs. Alkali metal heat pipe solar absorbers have been analyzed and tested by DOE contractors under the ASCS [9] program, Sandia National Labs, NASA, Argonne National Labs, Los Alamos National Labs [10], and other institutions [11] over a three decade period. Gas-heating solar receivers have likewise received significant attention over past decades for Brayton, Stirling, and indirect cycles, and recently have been identified by the DOE as one of the three likely technology paths towards the next generation receiver for use with high efficiency CSP systems.…”
Section: Executive Summarymentioning
confidence: 99%
“…The system had been able to exhibit good temperature uniformity and excellent thermal conductivity. Beforehand, in an investigation conducted by Boo et al [49] on loop heat pipes filled with different ratios of sodium. They concluded that the fill ratio has an effect on thermal resistance, effective thermal conductivity, startup time and as well as isothermal characteristics.…”
Section: Pvt System With Heat Pipementioning
confidence: 99%